Ischemic Stroke: New Neuron Recovery Approach with Mesenchymal and Neural Stem Cells - Angliana Chouw; Rina Triana; Nurrani Mustika Dewi; Siska Darmayanti; Miftakh Nur Rahman; Ardian Susanto; Bayu Winata Putera; Cynthia Retna Sartika (Cell and BioPharmaceutical Institute, 2018)
Stroke is a leading cause of death and long-term disability. This due to the ischemic event that cause by embolism of blockage blood flow. Thrombolytic agent plasminogen activator (tPA) is the only treatment approved by FDA. However, the used of tPA is limited to the short time window period. Neural stem cells (NSCs) show the potential to repair neuronal damage naturally after stroke. However, isolating NSCs is a challenging process due to the limitations of the method and its invasiveness. Some studies that had used mesenchymal stem cell (MSCs) as the main source of stem cell for therapy show that MSCs have the potency to differentiate into NSCs. in vitro, a differentiation process from MSC to NSC has been developed by combining the supplement or growth factor needed in the culture media.Keywords: stem cells, neuron stem cell, mesenchymal stem cell, stroke, trans-differentiation